Chemoradiation for High-grade Neuroendocrine Carcinoma of the Rectum and Anal Canal. (December 2017) - Voong, K. Ranh; Rashid, Asif; Crane, Christopher H.; Minsky, Bruce D.; Krishnan, Sunil; Yao, James C.; Wolff, Robert A.; Skibber, John M.; Feig, Barry W.; Chang, George J.; Das, Prajnan
Abstract : Objectives: We evaluated outcomes in patients with high-grade neuroendocrine (HGNE) carcinoma of the anorectum treated with pelvic chemoradiation. Materials and Methods: Between January 1, 2000 and February 17, 2013, 10 patients were confirmed to have HGNE carcinoma of the rectum or anal canal and treated with pelvic chemoradiation (radiation dose ≥45 Gy). Overall survival (OS), locoregional control (LRC), progression-free survival (PFS), and patterns of failure were evaluated. Results: Eight had pure HGNE carcinoma and 2 had HGNE carcinoma with minor component of adenocarcinoma. Median age was 62 years. Median follow-up was 15 months (range, 3 to 128 mo). Tumor stages included TxN0M0 (1), II (1), III (4), and IV (4) including 2 with only inguinal involvement. Median tumor size was 5.5 cm (range, 3 to 7 cm). Patients received postoperative chemoradiation (1), preoperative chemoradiation (2), and chemoradiation without surgery (7). Median dose was 50.4 Gy (range, 45 to 60 Gy). All patients received chemotherapy before or after chemoradiation. Seven had pelvic LRC; 2 had possible and 1 had confirmed local progression. Both patients who had preoperative chemoradiation only had microscopic focus of residual carcinoma at surgery. Seven had disease progression; of which all developed distant progression, with distant progression occurring as the first event in 6 (liver, lung, bone, and abdominal nodes). Actuarial 2-year PFS and OS were 30% and 46%, respectively. One patient received prophylactic cranial irradiation; only one of the other 9 patient developed brain metastasis. Conclusions: Pelvic chemoradiation provided LRC for the majority of the patients' lifetime. Most patients had distant failure, but patterns of distant failure do not support routine prophylactic cranial irradiation.